Diosmin Enhances the Anti-migration Activity of Curcumin Analog PGV-1 on Colorectal Cancer Cells - Ikawati, Muthi; Utomo, Rohmad Yudi; Hapsari, Novia Permata; Meiyanto, Edy; Oka, Chio (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Diosmin enhances the cytotoxicity of Pentagamavunone-1 (PGV-1) in cancer cells. PGV-1 and diosmin are predicted to target several matrix metalloproteinases (MMPs) in metastatic cancer, including colorectal cancer, but the anti-migration potency of their combination has not established yet. This study evaluates the anti-migration effect of PGV-1 and diosmin combination in colorectal cancer.METHODS: The cytotoxicity assay using Cell Counting Kit 8 (CCK-8) method in WiDr colorectal cancer cells was carried out to determine the concentration for anti-migration experiments. The wound healing assay was used to observe the anti-migration activity by measuring the cell-free area. Gelatin zymography was employed to detect the MMP activity indicating by the clear band density. The interaction between PGV-1 or diosmin and MMP proteins was predicted by molecular dockings.RESULTS: PGV-1 was cytotoxic (IC50 17 mM), while diosmin up to 100 mM did not affect cell viability. Both 10 mM PGV-1 as well as 50 and 100 mM diosmin slowed down the closure of cell-free area. A 100 mM diosmin was significantly enhance the anti-migratory activity of 50 and 100 mM PGV-1. The activity of MMP-9 and MMP-2 was also lower in the presence of diosmin compared to than that of PGV-1 alone. PGV-1 or diosmin was also able to interact with MMP proteins with a lower energy compared to than that of the native ligands.CONCLUSION: Diosmin enhances the anti-migration activity of PGV-1 in WiDr cells, possibly by affecting MMPs’ activity. This study is an evidence that diosmin is a potential co-chemotherapy candidate for PGV-1, that can be utilized to overcome metastatis in colorectal cancer.KEYWORDS: cancer, citrus flavonoid, co-chemotherapy, diosmin, matrix metalloproteinases (MMPs), migration, Pentagamavunone-1, WiDr cancer cell